“May God Bless Us, So That All the Ends of the Earth Will Fear Him!” (Ps 67:8): The Spatial Perspective in the Eschatological Vision of God’s Universal Rule in the Cluster of Psalms 65–68: Festschrift for GTM Prinsloo - Botha, Phil J. (Journal for Semitics, 2022)
Psalms 65–68 form a tight collection or “cluster” of psalms close to the conclusion of Book II of the Psalter. The implied redactors’ purpose with this cluster was to offer thanksgiving and praise to God for manifesting his eschatological rule over the entire world. This article investigates the function of spatial descriptions in defining God’s rule over the cosmos in these four psalms. After establishing harmony in the world, God is present as King in his temple in Zion. To dwell in his vicinity is the pinnacle of his people’s blessing and privilege. Further away from Jerusalem, all nations, even to the ends of the earth, worship and praise God and bring him gifts. There is a centripetal movement of joy, worship, praise, and tribute toward God from all who accept his benevolent rule over the world, but also a centrifugal movement away from him by those who oppose his rule and refuse to accept it.
free
Keywords: Psalms 65–68; YHWH’s eschatological rule; Zion; cosmos; pilgrimage of the nations; spatial perspective